2022
DOI: 10.1177/03635465221131551
|View full text |Cite
|
Sign up to set email alerts
|

The Predicted Position of the Knee Near the Time of ACL Rupture Is Similar Between 2 Commonly Observed Patterns of Bone Bruising on MRI

Abstract: Background: Bone bruises observed on magnetic resonance imaging (MRI) can provide insight into the mechanisms of noncontact anterior cruciate ligament (ACL) injury. However, it remains unclear whether the position of the knee near the time of injury differs between patients evaluated with different patterns of bone bruising, particularly with regard to valgus angles. Hypothesis: The position of the knee near the time of injury is similar between patients evaluated with 2 commonly occurring patterns of bone bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…In support of this hypothesis, studies that analyzed bone bruise patterns in ACL-injured participants have suggested that the knee was positioned in extension near the time of noncontact ACL rupture. 47,48,62…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, studies that analyzed bone bruise patterns in ACL-injured participants have suggested that the knee was positioned in extension near the time of noncontact ACL rupture. 47,48,62…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior studies, 16,19 the minimum sample size to detect 3° of valgus difference between the two groups with 80% power was 15 per group. We stated that “20 patients who displayed the 3–bone bruise pattern and 30 patients from a previous study 19 who displayed the 4–bone bruise pattern were included in this analysis.” 15 The number “136” appears in this paper once in the following sentence that addresses previous findings from Kim-Wang et al 14 : “Among a cohort of 136 patients with noncontact ACL injuries, these 2 bone bruising patterns comprised 59% of the patient cohort.” 15 Our methods detail the patient sample and appropriately reference our previously reported data related to bone bruising patterns. 14,19…”
Section: The Claim That the Numbers “Don’t Add Up”mentioning
confidence: 65%
“…We agree that the numbers used by Drs Hewett and Lavender “do not add up.” This is because the numbers cited by Drs Hewett and Lavender do not pertain to the study that is the topic of their letter. In brief, the study by Owusu-Akyaw et al 19 (2018) included 30 patients; the study by Kim-Wang et al 14 (2021) included 136 patients; and the study in question, that by Kim-Wang et al 15 (2023), included 50 patients. The study with 136 patients was a descriptive study of bone bruise patterns.…”
Section: The Claim That the Numbers “Don’t Add Up”mentioning
confidence: 99%
See 2 more Smart Citations